PERANCANGAN VISUAL BRANDING VIDEO SMOKEBELT GARAGE BERBASIS FEATURE SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Hendrawan, Denny; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
Smokebelt Garage is a Custom Culture motorcycle modification workshop. Custom culture is a term for a new American neologism that describes artwork, vehicles, hairstyles and fashion from people who drive and modify motorcycles and cars in the United States from the 1950s to the present. The research was conducted by using qualitative research method that is by conducting interview, observation, documentation, and literature study to get the data used as supporting the making of video design concept of Featue Smokebelt Garage. The result of this design is to design visual branding with videography media from smokebelt garage as an effort to add customer and increase customer loyalty.Kata kunci: Desain, Video Feature, Smokebelt garage